Effective Recovery of Palladium(II) Ions using Chitosan-Based Adsorbent Material - Rokiy Alfanaar; Krisfian Tata Aneka Priyangga; Arif Cahyo Imawan; Jumina Jumina; Yehezkiel Steven Kurniawan (Pandawa Institute, 2023)
Chitosan is one of the naturally abundant, biodegradable, and low-cost adsorbent materials for metal adsorption purposes. In this work, we evaluated the application of chitosan materials derived from seafood wastes in Depok beach, Yogyakarta, for an effective recovery of the palladium(II) ions. First of all, the seafood wastes were treated to obtain chitin and then followed by the deacetylation process to produce chitosan material with a deacetylation degree of 78.42%. The chitosan material was characterized using Fourier transform infrared (FTIR) spectrophotometer. It was found that chitosan gave high adsorption percentage (90%) for palladium(II) ions due to the complexation with hydroxyl, amino and carbonyl functional groups. The palladium(II) adsorption onto chitosan material followed the pseudo-second-order (R2 = 0.9978) and Langmuir (R2 = 0.9979) models for kinetic and isotherm experiments, respectively, with a maximum adsorption capacity value of 0.70 mmol g-1. The palladium(II) ions could be easily desorbed in 90% percentage using 1.0 M HCl solution from metal-laden chitosan to regenerate the adsorbent material. The chitosan-based adsorbent material did not lose its adsorption capability after three consecutive cycles with no significant structural change as revealed from the FTIR data. These results showed the potential application of natural chitosan materials derived from seafood wastes for the effective recovery of palladium(II) ions.